Cultura de segurança do paciente: percepções e atitudes dos trabalhadores nas instituições hospitalares de Santa Maria - Baratto, Mari Angela Meneghetti (2015)
Patient safety culture is a key component to the quality of health services. This study aims to analyze the attitudes and perceptions of professionals working directly or indirectly in the care of the hospitalized patient regarding the patient safety culture. This is a cross-sectional study, conducted in 2014, with professionals in the field of health and support services in seven hospitals in Santa Maria, Rio Grande do Sul, Brazil. As a research tool, used the Brazilian version of the Safety Attitudes Questionnaire (SAQ) and sociodemographic and labor issues of workers. Data were organized in Epiinfo 6.04® program, and doubled entered independently. After the correction of errors and inconsistencies, conducted the analysis in PASW Statistic® program, using descriptive and analytical statistics. The cutoff for positive assessment of safety culture was ≥ 75 points. The SAQ was measured by the total score and its six areas. As a result, participated in the study 2,634 professionals, having female predominance (72.6%), aged between 19 and 38 years (50.9%), working in mixed shifts (45.1%), contact the patients (71.6%), which did not have another job (79.9%) and have no overtime work (66.2%). The internal consistency of the SAQ was 0.90. The total score SAQ ranged from 13.9 to 97.9, with an average of 70.1 and a mean of 68.4 (± 13.4). Positive evaluation is evidenced in the fields working as a team and Climate Job satisfaction, with an average of 75 and 90 respectively, indicating that, as much as there are difficulties in the workplace, professionals expressed happiness for what they do, valued colleagues and the place in which they worked. The other areas negatively rated for safety culture (<75). The Hospital Management Perception domain had the lowest score (average 60). When the two professional groups being compared (health and support), we identified little variability in the assessment of areas, although the support of professionals tend to lower scores. The results presented should not be analyzed in isolation, but as backings for the enactment of improvement initiatives in order to improve the quality of patient care and professionals.